Effectiveness of Health Education on Knowledge Regarding Prophylaxis against Rabies in School Children - Ravish S Hardanahalli; Jayanthi Srikanth; Gangaboraiah Anandaiah; Rachana Annadani; V Veena; Rupsa Banerjee Banerjee (Medsci Publications, 2017)
Introduction: School children are at risk for exposure to dogs because of their playful nature and unable to protect themselves. Seeking timely and correct post-exposure prophylaxis is necessary to prevent rabies. In this background, the present study was conducted to assess the knowledge of school children and to know the effectiveness of health education on improvement in their knowledge. Methods: The study included 121 high school children of an urban poor locality in Bangalore. All of them were administered pre-test using a self-administered questionnaire in the local language and the knowledge was assessed. Later, health education session was conducted regarding prevention of rabies. Subsequently, 3 months later, post-test was administered to the same study subjects. The data was recorded and analysed. The descriptive statistics was computed and the student paired T - test was used to compare pre & post- test score. Results: The mean score of knowledge in the pre- test was 12.02 out of 20 and after health education session, the post- test score increased significantly to 16.94. Conclusions: Knowledge on prophylaxis against rabies improved after health education. Therefore, health education sessions should be conducted in all the schools, to prevent rabies among this vulnerable group.